Using Theory to Guide Practice in Children’s Pedestrian Safety Education - Cross, D.; Hall, M.; Howat, Peter (American Alliance for Health, Physical Education, Recreation, and Dance, 2003)
Few pedestrian injury prevention programs appear to articulate the theory upon which their design and evaluation are based. This article describes how theory was used to plan, develop, implement, and evaluate the educational component of a comprehensive child pedestrian intervention. Organizational and planning theories were used to guide the conceptual development, implementation, and evaluation of the program, while behavioral and child development theories were used to identify the content and strategies to address the pedestrian behavior of seven to nine year old children. The resultant program demonstrated improved road crossing and playing behaviors in the intervention group children compared to those in the comparison group. The systematic use of relevant theory in this program is likely to be associated with its positive impact on children's pedestrian safety.